Efficacy and safety of medium-dose UVA1 phototherapy in recalcitrant prurigo nodularis: A case report - Nuntawisuttiwong, Nattaporn; Yothachai, Punyanut; Pruksaeakanan, Chutipon; Silpa-archa, Narumol (Thai Journal of Dermatology, 2019)
Prurigo nodularis (PN) is a chronic, pruritic skin condition that is characterized by firm, dome-shaped papules and nodules with varying degrees of central scale, crust, erosion, and ulceration, typically showing a symmetrical distribution. The nodules are intensely pruritic, which leads to the induction of a vicious itch-scratch cycle and reduces quality of life. Although the etiology and pathogenesis remain unclear, cutaneous inflammation and neuronal plasticity seem to play a crucial role in PN1. Treatment of PN is challenging because it is usually difficult and requires a multifaceted approach. The most common treatment options include oral antihistamines and topical or systemic corticosteroids. Phototherapy treatment, such as with narrowband ultraviolet B (NB-UVB) and psoralen and ultraviolet A (PUVA), has been used as a therapeutic alternative in patients with multiple comorbidities or generalized PN2; however, studies on ultraviolet A1 (UVA1) phototherapy are still limited owing to a paucity of randomized controlled trials. We report on a patient with relapsed, severe PN who had undergone a variety of treatments (oral antihistamines; a topical, super-potent corticosteroid; short courses of systemic corticosteroids; and NBUVB phototherapy) and subsequently achieved improvement with UVA1 phototherapy.